The Effect of Organic and Inorganic Fertilizer Applications on N, P and K Uptake and Yield of Sweet Corn (Zea mays saccharata Sturt) - Emma Trinurani Sofyan; Dirga Sapta Sara (JOURNAL OF TROPICAL SOILS, 2018)
To overcome insufficient sweet corn production in Indonesia, various strategies have been developed to improve its production. This study was conducted to evaluate the effect of organic fertilizer (i.e. cow manure) and inorganic fertilizer application on nutrient uptake and yield of sweet corn (Zea mays saccharata Sturt). Inceptisol possess low soil fertility and relatively low to moderate level of organic matter content. Application of organic fertilizer in combination with inorganic fertilizers is expected to increase N, P and K uptake and yield of sweet corn. This study was conducted from October 2016 to February 2017 at the Field Experimental Station of Agriculture Faculty, Universitas Padjadjaran in Jatinangor, West Java. The study was performed in a Randomized Block Design consisting of 10 treatments and 3 replications. The treatments were as follow: A = Control, B = Standard NPK, C = 0 NPK + 1 organic fertilizer, D = ¼ NPK + 1 organic fertilizer, E = ½ NPK + 1 organic fertilizer,  F = ¾ NPK + 1 organic fertilizer, G = 1 NPK + 1 organic fertilizer, H = ¾ NPK + ¼ organic fertilizer, I = ¾ NPK + ½ organic fertilizer and J = ¾ NPK + ¾ organic fertilizer. The results showed that the treatment I (¾ NPK + ½ organic fertilizer) resulted in the highest N, P and K uptake, i.e. 54.31 mg plant-1; 82.85 mg plant-1 and 56.40 mg plant-1, respectively and the heaviest weight of sweet corn, i.e. 407.33 g.